DEBIRI plus capecitabine: a treatment option for refractory liver-dominant metastases from colorectal cancer. (July 2019) - Di Noia, Vincenzo; Basso, Michele; Marsico, Valentina; Cerchiaro, Eleonora; Rossi, Sabrina; D'Argento, Ettore; Strippoli, Antonia; Schinzari, Giovanni; Iezzi, Roberto; Cassano, Alessandra; Barone, Carlo
Aim: This single institution Phase II study evaluated drug-eluting beads loaded with irinotecan (DEBIRI) plus capecitabine in pretreated patients with colorectal cancer liver metastases.Patients & methods: Forty patients with liver-limited or liver-dominant disease, who have failed at least two previous lines of chemotherapy, underwent either four DEBIRI at 2-week interval or two DEBIRI every 4 weeks for bilobar or single-lobe metastases, respectively. Capecitabine was given at 1000 mg/m 2 twice-daily on days 1–14 every 3 weeks.Results: Seven partial responses and 12 stable diseases were observed, achieving a disease control rate of 47.5%. Median progression-free survival and overall survival resulted 4 and 8 months, respectively. Grade 3 adverse events occurred in 6/40 points (15%) of patients.Conclusion: DEBIRI plus capecitabine is a valid treatment option for heavily pretreated patients with colorectal cancer liver metastases.